Face and Ethnical Group Recognition with Images of Different Resolutions - Lu, Chong; Ren, Yan; Han, Liying (Archives of Business Research, 2021)
In this paper, a dataset for Xinjiang minority ethnical groups is introduced, and implementation of two dimensional Linear Discriminant Analysis (2DLDA) and two-dimensional Partial Least Squares (2DPLS) is investigated. Two important topics for face recognition and the ethnicity recognition are investigated for database with different image resolutions. Experiments show that 2DLDA performances better than 2DPLS on our face database.